Accidental hydrogen release in a gas chromatograph laboratory: A case study. (16th March 2017) - Henriksen, M.; Bjerketvedt, D.; Vaagsaether, K.; Gaathaug, A.V.; Skjold, T.; Middha, P.
Abstract: A 50-litre standard hydrogen gas cylinder was temporarily placed in a laboratory to supply hydrogen gas to a flame ionization detector (FID) for use in gas chromatography (GC). On 20 January 2015, the safety relief valve on the pressure regulator failed and released about 0.34 kg of hydrogen into the laboratory. The gas cloud did not ignite so there was no injury or damage. The results of a full investigation with a complete course of action and reconstruction are presented that verify the cause of the leakage and estimate the gas concentration of the dispersion and gas cloud. A preliminary simulation of the likely explosion is provided. If the gas cloud had ignited, the explosion would most likely have caused significant structural damage to doors, windows, and possibly the walls. Highlights: Full investigation and detailed description of an accidental hydrogen release. Positive identification of leakage point and mass released. Both analytical calculation and CFD simulation of possible explosion pressures. Summarized lessons learned for the incident.